2001
DOI: 10.1002/cne.1042
|View full text |Cite
|
Sign up to set email alerts
|

Selective synaptic distribution of AMPA and kainate receptor subunits in the outer plexiform layer of the carp retina

Abstract: The subunit composition of ionotropic glutamate receptors (GluRs) is extremely diverse and responsible for the diversity of postsynaptic responses to the release of glutamate, which is the major excitatory neurotransmitter in the retina. To understand the functional consequences of this diversity, it is necessary to reveal the synaptic localization and subunit composition of GluRs. We have used immuno light and electron microscopy to localize AMPA and kainate (GluR1, GluR2/3, GluR4, GluR5-7) subunits in identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
2
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 60 publications
4
23
2
1
Order By: Relevance
“…The patterns described in the present study are in good agreement with earlier reports (Hughes et al, 1992;Mü ller et al, 1992). At the protein level, the localization of AMPA-type GluRs in the retina has been described for cat Morigiwa and Vardi, 1999;Qin and Pourcho, 1999a,b), rat (Peng et al, 1995;Vardi et al, 1998;Hack et al, 1999;Qin and Pourcho, 1999a), goldfish (Peng et al, 1995;Schultz et al, 1997;Vardi et al, 1998;Yazulla and Studholme, 1999;Qin and Pourcho, 1999a,b;Vandenbranden et al, 2000), and carp (Schultz et al, 2001). We will, therefore, restrict the discussion mainly to the localization of AMPA-type GluR subunits in the outer retina with respect to their localization in bipolar cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The patterns described in the present study are in good agreement with earlier reports (Hughes et al, 1992;Mü ller et al, 1992). At the protein level, the localization of AMPA-type GluRs in the retina has been described for cat Morigiwa and Vardi, 1999;Qin and Pourcho, 1999a,b), rat (Peng et al, 1995;Vardi et al, 1998;Hack et al, 1999;Qin and Pourcho, 1999a), goldfish (Peng et al, 1995;Schultz et al, 1997;Vardi et al, 1998;Yazulla and Studholme, 1999;Qin and Pourcho, 1999a,b;Vandenbranden et al, 2000), and carp (Schultz et al, 2001). We will, therefore, restrict the discussion mainly to the localization of AMPA-type GluR subunits in the outer retina with respect to their localization in bipolar cells.…”
Section: Discussionsupporting
confidence: 93%
“…The GluR2/3 immunoreactivity was depicted as being concentrated at the site of the invagination of the dendrite into the rod spherule, and appears to differ from the localization of GluR2 at noninvaginating dendrites (Hack et al, 1999). In the carp, ON-and OFF-bipolar processes contacting red cones were GluR2/3-IR (Schultz et al, 2001). …”
Section: Glur2mentioning
confidence: 99%
“…Also, our fixation was from 30 min to 60 min, a condition that reduced GluRl-IR in goldfish (VandenBranden et al, 2000a). Recently, Schultz et al (2001) used an antiserum against GluRl from PharMingen at 1: 500 in carp retina. They also report weak somatic labeling and no labeling in either plexiform layer.…”
Section: Glycinergic Systemmentioning
confidence: 99%
“…3A). Fret43 is an antiserum that marks the pedicles of red-and green-sensitive cones in carp retina (Schultz et al, 2001), and double-labeling experiments confirmed the presence of Caldendrin in cone pedicles (Fig. 3B).…”
Section: Synaptic Localization Of Caldendrinmentioning
confidence: 68%
“…In cone pedicles, label was typically concentrated in elements lateral to the synaptic ribbons (Fig. 4A,B), which were identified as horizontal cell terminals on the basis of their shape and location (Stell, 1975;Schultz et al, 2001). Label was confined to the membrane and a narrow band of cytoplasm in close proximity to the membrane and was most prominent at the tips of spinules and along the membranes facing the releasing site of neurotransmitter of the cones.…”
Section: Synaptic Localization Of Caldendrinmentioning
confidence: 97%